Characterizing the subcellular localization and function of Citron Kinase in the germline of Drosophila melanogaster - Porter, Kyra M. (East Carolina University, 2023)
Cytokinesis, or the final division of cells, is a conserved and highly regulated process that is crucial for all multicellular organisms. Errors in cytokinesis are linked to a variety of maladies, including microcephaly and chromosome abnormalities such as polyploidy and aneuploidy. Eukaryotes have a dynamic structure called the actin-myosin contractile ring that is responsible for separating the two daughter cells upon the completion of the final phase of mitosis. The proper positioning and timing of the contractile ring is crucial to the dividing cell. Contractile ring assembly is regulated, at least in part, by Citron Kinase, which organizes actin formation. During traditional (complete) cytokinesis, the contractile ring is the machinery responsible for the total separation of daughter cells from one another. Intriguingly, germ cells exhibit incomplete cytokinesis, in which the dividing cell never fully abscises from its daughter, which effectively tethers cells in a nest (called a cyst). The cyst is joined by intracellular canals that are stabilized by the ring canals. Cyst formation is necessary for germ cell differentiation into oocytes. Whether and how Citron Kinase controls this modified cytokinesis in these unique cells is unclear. Here, I use the model organism Drosophila melanogaster to investigate my hypothesis that Citron Kinase is required for proper cyst formation. To compare the localization of the protein in germ cells that undergo complete versus incomplete cytokinesis, I used the UAS-Gal4 system to over-express a fluorescently tagged version of Citron Kinase in the Drosophila germline. Then, to visualize the changes in germ cell division that occur in the absence of Citron Kinase, I used the UAS-Gal4 system in conjunction with RNA interference (RNAi) to knock down Citron Kinase, depleting its mRNA. My findings show that Citron Kinase is localized to the fusomes and the cytoplasm in both germline stem cells (GSCs) and dividing cysts, and to the ring canals of dividing cysts. Moreover, when Citron Kinase is lost, females exhibit a complete loss of germ cells, indicating that Citron Kinase has a larger role in female fecundity that has yet to be explored.
Keywords: germline stem cells; incomplete cytokinesis; ring canals